Image of Lakulisa on the Lalatabimba of the Garbhagriha - Temples of India Project Team (Jio Institute, 2024)
The lalatabimba (lintel) of the garbhagriha (sanctum sanctorum) has an image of Lakulisa—a preceptor of the doctrine of the Pashupata tradition of Shaivism—seated in padmasana (lotus pedestal pose). He is shown with an erect phallus, holding a lakuta (staff) in his left hand and a beejapurak or phala (fruit) in his right hand.